Upaya Meningkatkan Prestasi Belajar IPS Materi Pahlawan Nasional melalui Penerapan Model Pembelajaran Terarah pada Siswa Kelas VII.7 SMP Negeri 11 Binjai Tahun Pelajaran 2019/2020 - Surya Dharma Tarigan (Keguruan, 2022)
Target-oriented learning in mastery of the material proved successful in 'short-term remembering' competitions, but failed to equip children to solve problems in long-term life. The aims of this study are: (a) to determine the increasing in Social Science learning achievement after the application of the directed teaching model active learning method, (b) to determine the effect of Social science learning motivation after the active learning directed teaching model was applied. This research used three rounds of action research. From the results of the analysis, it was found that student achievement increased from Pre-Cycle to Cycle-II, namely, Pre-Cycle (62.5%), Cycle I (75%), Cycle II (93.75%). The conclusion of this study is the active learning method with a directed teaching model can have a positive effect on the learning motivation of SMP Negeri 11 Binjai students, and this learning model can be used as an alternative for social studies learning.